PERUBAHAN KADAR KOLESTEROL SERUM PADA TIKUS SETELAH MENGKONSUMSI MALTOOLIGOSAKARIDA YANG DISINTESIS SECARA ENZIMATIK MENGGUNAKAN AMILASE Bacillus licheniformis BLl [The Change of Serum Cholesterol Level in Rats after Consuming Maltooligosaccharide Synthesized by Enzimatic Reaction of Bacillus licheniformis BLl Amylase] - Dinoto, Achmad; Rahayu, Rita Dwi; Satyaningtijas, Aryani S (Research Center for Biology-Indonesian Institute of Sciences, 2010)
To investigate the impact of consuming enzymatically synthesized maltooligosaccharide using Bacillus licheniformis BLl amylase on reduction of serum cholesterol level, in preclinical study groups of Sprague Dawley rats were fed for 3 weeks with four different test diets: basal diet (BD), high serum cholesterol-stimulating basal diet (CD), high serum cholesterol-stimulating basal diet supplemented with 3% (w/w feed) commercial maltooligosaccharide (CI), and high serum cholesterol-stimulating basal diet supplemented with 3% (w/w feed) maltooligosaccharide synthesized by enzimatic reaction of B. licheniformis BLl amylase (CB).Our result shows a reduction of serum cholesterol level up to 39.1% in rats CB after three weeks consuming maltooligosaccharide synthesized using B. licheniformis BLl amylase. In addition, significantly increased blood glucose level was not found in this study as an impact of consuming maltooligosaccharide synthesized using B. licheniformis BLl amylase.